Technical illustration in bicycle design [electronic resource] - Tan, Siang Liong, 1988-; Idris Ishak, supervisor; Fakulti Kejuruteraan Mekanikal (2011)
Project Paper (Sarjana Muda Sains (Rekabentuk Industri)) - Universiti Teknologi Malaysia, 2011